High-growth entrepreneurial firms in Africa: A quantile regression approach - Micheline Goedhuys; Leo Sleuwaegen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper studies the growth performance of a large set of entrepreneurial firms in ten manufacturing sectors of eleven Sub-Saharan African countries. The focus of the paper is on identifying those entrepreneurs' attributes and firm characteristics that tend to generate a significant number of high-growth firms in these countries. To this end, we use a quantile regression, which provides a more complete estimation of the growth distribution of firms conditional on different attributes. The results indicate that especially firms that engage in product innovation, have their own transport means and are connected to the internet through their own website are characterized by higher growth rates and display a more skewed distribution to the right, hosting a higher number of high-growth firms.
Keywords: D92; O55; 330; quantile regression; high-growth firms; firm growth; Africa; Unternehmenswachstum; Verarbeitendes Gewerbe; Afrika südlich der Sahara